Describing Dolphin Interactions with Cypriot Fisheries Using Fishers’ Knowledge - Marios Papageorgiou; Soteria-Irene Hadjieftychiou; Chistodoulos Christodoulou; Antonis Petrou; Dimitrios K. Moutopoulos (Journal of Marine Science and Engineering)
The study explores the interactions between dolphins and Cypriot fisheries, emphasizing the economic impact and fisher perceptions through data collected from structured interviews with small-scale and large pelagic fishers. The research documents frequent dolphin interactions, impacting catch and gear in both fishing sectors. Reported financial losses and gear damage highlight a significant economic burden, with annual losses averaging EUR 6144 for small-scale and EUR 29,882 for large pelagic fishers. Efforts to mitigate these interactions, such as using acoustic deterrents, have shown mixed results, reflecting dolphins’ adaptability to human activity. While some fishers use deterrents, others remain hesitant due to cost and inconsistent efficacy. The study underscores the need for improved, sustainable solutions that integrate fisher input to enhance acceptance and effectiveness. Findings suggest that dolphins are increasingly relying on fishing activities as a foraging strategy, aligning with broader trends in the Mediterranean. In the context of EU Directive 2014/89/EU, the study integrates ecological considerations and socioeconomic impacts to ensure balanced marine management strategies. This work emphasizes the complexity of human–wildlife conflicts in marine environments, suggesting that further research and collaboration with fishers are essential to developing adaptive strategies that balance conservation with the economic needs of local fishing communities.